Fulminant arterial vasculitis as an unusual complication of disseminated staphylococcal disease due to the emerging CC1 methicillin-susceptible Staphylococcus aureus clone: a case report - Vidal, Charles (BMC Infect Dis, 2019)
BACKGROUND: Staphylococcus aureus has emerged as a leading cause of invasive severe diseases with a high rate of morbidity and mortality worldwide. The wide spectrum of clinical manifestations and outcome observed in staphylococcal illness may be a consequence of both microbial factors and variability of the host immune response. CASE PRESENTATION: A 14-years old child developed limb ischemia with gangrene following S. aureus bloodstream infection. Histopathology revealed medium-sized arterial vasculitis. The causing strain belonged to the emerging clone CC1-MSSA and numerous pathogenesis-related genes were identified. Patient’s genotyping revealed functional variants associated with severe infections. A combination of virulence and host factors might explain this unique severe form of staphylococcal disease. CONCLUSION: A combination of virulence and genetic host factors might explain this unique severe form of staphylococcal disease.